Unilateral laminectomy approach for total resection of intradural extramedullary spinal tumor - Steven Awyono; Putu Eka Mardhika; Tjokorda Gde Bagus Mahadewa; Akbar Wido; Hizkia Lumban Gaol; Intan Permata Wijaya (Neurologico Spinale Medico Chirurgico, 2019)
Spinal tumors found in about 5-15% of the central nervous system neoplasm. Intradural-extramedullary spinal cord tumors are one of the types that usually managed with total laminectomy but with many postoperative complications. A 76-year-old woman with paraplegia caused by intradural-extramedullary intraspinal tumor at thoracic 4 level. For this patient, we performed unilateral laminectomy without any fusion or stabilization from the left side then we performed total excision of the tumor. The surgery was successfully done with fast improvement of patient condition, minimal pain after surgery, no blood transfusion needed, shorter intensive care period needed, and fast recovery time are the prominent things in this case. Three days after surgery, the patient’s motoric power already improved and then the patient is permitted to go home at the fifth day.